Budaya Penegakan Hukum Pada Kepolisian Dalam Penanganan Kasus Pidana - Purnomo Adi Nugroho; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research was conducted to find out about the legal culture in the police institution in handling criminal cases. Law is a regulation in the form of norms and sanctions, written and unwritten, which is made with the aim of regulating human life to maintain order and security and prevent crime. Culture is the overall attitude and pattern of behavior and knowledge which is a habit that is inherited and owned by certain individuals or groups. Legal culture is one of the important aspects that must be considered by law enforcement officers in carrying out law enforcement, a culture consisting of values and attitudes that can affect the way the law works. By paying attention to and reviewing the weaknesses that exist in this aspect of legal culture, it is hoped that in the future law enforcement officers can change paradigms and perspectives, not only individually but also institutionally in order to create progressive law so that law enforcement can achieve the desired goals. is to create a just and prosperous society.